2013
DOI: 10.5009/gnl.2013.7.5.560
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cochinchina momordica Seed Extract on Gastric Acid Secretion and Morphologic Change in Aged Rat Stomach

Abstract: Background/AimsCochinchina momordica seed extract (SK-MS10) has a gastric protective effect. We aimed to assess the effect of SK-MS10 on gastric acid secretion with morphologic changes in the aged rat.MethodsAcid secretions were evaluated in the male F344 rats of four different ages (6-, 31-, 74-week, and 2-year). The 31-week-old rats were divided to three groups and continuously administered chow containing vehicle, SK-MS10 and lansoprazole, respectively. At the age of 74 weeks and 2 years, basal and stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…In the present study, we found that continuous administration with PMK-S005 reverse the decrease of age-related gastric acid concentration in 74-week-old rats and PMK5 group was more potent than PMK10 group. However, these effects did not more influential in the 2-year-old rats which are comparable to our previous SK-MS10 data 29. In addition, age-related increment of connective tissue in lamina propria seems to be attenuated in PMK5 group in 74-week and 2-year-old rats but the effect was not that apparent (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present study, we found that continuous administration with PMK-S005 reverse the decrease of age-related gastric acid concentration in 74-week-old rats and PMK5 group was more potent than PMK10 group. However, these effects did not more influential in the 2-year-old rats which are comparable to our previous SK-MS10 data 29. In addition, age-related increment of connective tissue in lamina propria seems to be attenuated in PMK5 group in 74-week and 2-year-old rats but the effect was not that apparent (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…We previously reported that Cochinchina momordica seed extract (SK-MS10) attenuated connective tissue change with age and kept the capacity of acid secretion to that of young age, suggesting that SK-MS10 might be an antiaging agent in the stomach as well as mucoprotective agent 29. In the present study, we found that continuous administration with PMK-S005 reverse the decrease of age-related gastric acid concentration in 74-week-old rats and PMK5 group was more potent than PMK10 group.…”
Section: Discussionmentioning
confidence: 99%
“…One gram lansoprazole was mixed with 20 kg rat chow to obtain the daily dose. A recent study from our group of the long-term (1.5 years) administration of lansoprazole 5 mg/kg/day found that 74-week old F344 rats in the lansoprazole group had lower stimulated gastric acid secretion than those in the vehicle group 10. In the present study, the rats were fasted but allowed water for 12 hours before the experiments.…”
Section: Methodsmentioning
confidence: 53%
“…Gastric hypochlorhydria in the elderly has been associated with the risk of developing SIBO 15,16. Recently, we evaluated gastric acid secretion in the male F344 rats of four different age groups (6-, 31-, and 74-week, and 2-year) and found that both basal and stimulated gastric acid secretions significantly decreased with increased connective tissue of lamina propria with age 10. Nevertheless, we observed that lansoprazole decreased stimulated gastric acid secretion in 74-week-old F344 rats 10.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, elevated gastric pH results in the increased bacterial colonization in the stomach 36 . This effect might be more severe in the aged since the gastric acid secretion decreased with age in rats 37 . In addition, chronic PPI treatment may reduce the function of neutrophils that produce reactive oxygen species, through the increase of the basal cytosolic calcium concentrations in the neutrophils 38 .…”
Section: Discussionmentioning
confidence: 99%